Definition of Islam and Concept of Justice - Paulus Satyo Istandar Tan (Faculty of Law, Universitas Pekalongan, 2020)
This research aims to detail the definition of Islam as a religion and explain its concept of justice. By exploring the views of the Quran, Hadith, and scholarly thought, this research will present a richer and more contextualised understanding of Islam and justice. The ultimate goal is to contribute more in-depth and applicable thinking to this concept in the context of contemporary society. This research adopts a qualitative approach to explore and interpret Islamic teachings. The research method used involves textual analysis of primary sources such as the Qur'an and Hadith, as well as references to the views of scholars. The textual analysis was conducted meticulously to understand the context and meaning contained in the texts. The study highlights the universal and coherent character of Sharia, which is designed to guide humanity across time and place. Crucially, justice and solidarity emerge as central themes in Islam, which resonate throughout the Qur'an and underscore the social mission of all prophets. It can thus be concluded that Islam, with its rich theological underpinnings and moral imperatives, plays an important role in shaping the beliefs, practices and worldviews of its followers.